Peningkatan Nilai Ekonomi Modifikasi Pati Umbi Taka (Tacca leontopetaloides (L.) Kuntze) Sebagai Bahan Baku Pembuatan Biskuit Herbal - Lubis, Novri Yanti; Fauziah, Nenden; Ilahi, Resa Restu; Rustamsyah, Ardi (Jurnal Sains dan Teknologi Pangan, 2019)
ABSTRACT This study aimed to observe the effect of the concentration of modified taka starch (Tacca leontopetaloides (L.) Kuntze) as well as the size of natural taka tubers and red ginger starch on the characteristics of the produced herbal biscuits. The taka starch was modified by using ginger oil components. Meanwhile, the size of natural taka tubers and red ginger starch granules was compared by using a scanning electron microscope. The study was classified into three stages, namely the taka starch manufacture, the taka starch modification, and the biscuit production. The results showed that the modified taka starch had a larger granule than the natural starch, with the size reached 36.9 µm and 34.4 μm, respectively. Meanwhile, the water, ash, fat, protein, and carbohydrate contents, as well as the calories reached 4.56%, 2.40%, 9.11%, 8.71%, 75.27 %, and 417.99 cal, respectively. In general, all parameters met the Indonesian National Standard for biscuits. Keywords: Biscuits, characteristics of starch granule, taka tuber ABSTRAK Penelitian ini ingin melihat pengaruh modifikasi pati taka (Tacca leontopetaloides (L.) Kuntze) dengan menggunakan komponen minyak jahe dan membandingkan ukuran granul pati umbi taka alami dan minyak jahe merah dengan menggunakan metode SEM (Scanning Electron Microscope), kemudian dijadikan produk pembuatan biskuit herbal. Metode penelitian diawali dengan pembuatan pati taka dan modifikasi pati taka kemudian dijadikan produk pangan. Pengujian karakterisasi pati taka dan pati taka termodifikasi dengan pengujan SEM menunjukkan, pati yang sudah dimodifikasi memiliki bentuk granul lebih besar 36,9 µm dari pati taka alami 34,4 µm. Hasil modifikasi pati umbi taka menghasilkan produk inovasi pangan berupa biskuit herbal, dengan hasil karakteristik meliputi kadar air 4,56%, kadar abu 2,40%, kadar lemak 9,11%, kadar protein 8,71%, kadar karbohidrat 75,27% dan kalori 417,99 kal. Secara umum, semua parameter sudah sesuai dengan SNI biskuit. Kata kunci: Biskuit, karakteristik granul pati, umbi taka